2017
DOI: 10.1155/2017/1305479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cleats-Surface Interaction on the Performance and Risk of Injury in Soccer: A Systematic Review

Abstract: Objective To review the influence of cleats-surface interaction on the performance and risk of injury in soccer athletes. Design Systematic review. Data Sources Scopus, Web of science, PubMed, and B-on. Eligibility Criteria Full experimental and original papers, written in English that studied the influence of soccer cleats on sports performance and injury risk in artificial or natural grass. Results Twenty-three articles were included in this review: nine related to performance and fourteen to injury risk. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The fact that most individuals with a LAS episode will sustain at least one additional sprain, with many developing CAI (Gribble et al, 2016), and that this condition increase the risk of LAS, corroborates the need of studying athletes with CAI also (Silva et al, 2017a). On the other hand, extrinsic factors such as cleatsurface interaction have been studied (Silva et al, 2017b), highlighting the need of identifying an easily modifiable risk factor that help players to reduce different injuries risk. A systematic review demonstrated that different cleat models have been evaluated in terms of risk of injury in cases of calcaneal apophysitis, repeated impact injuries, and knee and ankle injuries related to increased joint loading (Silva et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that most individuals with a LAS episode will sustain at least one additional sprain, with many developing CAI (Gribble et al, 2016), and that this condition increase the risk of LAS, corroborates the need of studying athletes with CAI also (Silva et al, 2017a). On the other hand, extrinsic factors such as cleatsurface interaction have been studied (Silva et al, 2017b), highlighting the need of identifying an easily modifiable risk factor that help players to reduce different injuries risk. A systematic review demonstrated that different cleat models have been evaluated in terms of risk of injury in cases of calcaneal apophysitis, repeated impact injuries, and knee and ankle injuries related to increased joint loading (Silva et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, extrinsic factors such as cleatsurface interaction have been studied (Silva et al, 2017b), highlighting the need of identifying an easily modifiable risk factor that help players to reduce different injuries risk. A systematic review demonstrated that different cleat models have been evaluated in terms of risk of injury in cases of calcaneal apophysitis, repeated impact injuries, and knee and ankle injuries related to increased joint loading (Silva et al, 2017b). However, only recently it has been demonstrated that in healthy athletes different cleat models aren't related to differences in ankle sprain risk factors (Silva et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…This evolution highlights the study of cleat-surface interaction involving artificial turf grounds. A recent systematic review indicates that this interaction has a significant impact on the performance of several sports gestures (straight-line sprints and slalom, kicking and passing a ball) in healthy athletes (Silva et al, 2017b). However, according to our knowledge, no study has assessed the cleatsurface interaction in athletes with one of the most frequent postural control disorder -chronic ankle instability.…”
Section: Introductionmentioning
confidence: 99%
“…Seeing the performance as one of the major athletes' concern (Hennig, 2011), it becomes relevant to study the factors that can influence this variable, not only in athletes without a history of ankle injury, but also in athletes suffering from CAI. The cleat-surface interaction has been the subject of several studies (Muller et al, 2010;Silva et al, 2017a;Sterzing et al, 2009;Sterzing et al, 2010), however, according to a recent systematic review (Silva et al, 2017b) this interaction was not evaluated in tasks closed to the ankle sprain injury mechanism such as jumps with changes of direction. Among the various features of the cleats, the sole importance has been highlighted and would have a significant impact on this task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation